Monetary war and peace London, Washington, Paris, and the Tripartite Agreement of 1936 - Harris, Max ca. 20./21. Jh (Studies in macroeconomic history, 2021)
The international monetary system imploded during the Great Depression. As the conventional narrative goes, the collapse of the gold standard and the rise of competitive devaluation sparked a monetary war that sundered the system, darkened the decade, and still serves as a warning to policymakers today. But this familiar tale is only half the story. With the Tripartite Agreement of 1936, Britain, America, and France united to end their monetary war and make peace. This agreement articulated a new vision, one in which the democracies promised to consult on exchange rate policy and uphold a liberal international system - at the very time fascist forces sought to destroy it. Max Harris explores this little-known but path-breaking and successful effort to revolutionize monetary relations, tracing the evolution of the monetary system in the twilight years before the Second World War and demonstrating that this history is not one solely of despair